Sanksi Terhadap Pelanggaran Izin Pengelolaan Sampah - Pintubatu, Meyliana; Salmon, Hendrik; Pattipawae, Dezonda Rosiana (Jurnal Saniri, 2023)
Increasing population and increasing community life activities in Ambon City, which results in more and more waste generation. The increase in the volume of waste is directly proportional to the increase in population. Waste management still relies on the final approach, namely waste is collected, transported and disposed of to the final processing site.Based on the description above, the issues that will be discussed are how to apply sanctions to violations of waste management permits and what are the legal consequences if sanctions are not applied to violations of waste management permits. The research used in this paper is normative legal research.The results of the research show that the government issued a Waste Management Law, in the law it states that everyone who carries out waste management business activities must have a permit from the local government. The Regional Regulation explains that everyone who carries out waste management business activities must have a permit from the regional head according to their authority. Law Number 18 of 2008 concerning Waste Management Article 17 paragraph (1), (2), (3). Ambon Mayor Regulation Number 39 of 2018 concerning Enforcement of Administrative Sanctions Against the Granting of Waste Management Permits. Article 2 paragraph (1). Regional Regulation Number 11 of 2015 concerning Waste Management Article 32 (1), (2), (3). The Ambon City Government issued Ambon Mayor Regulation Number 39 of 2018. As in the General Hospital in Tulehu and Siloam Hospital. The permit granted to Siloam Ambon Hospital for waste management seems to have not been implemented properly in accordance with the existing permit, there is a violation in the waste disposal process where waste originating from the hospital is dumped into the sea. Meanwhile, the General Hospital in Tulehu disposes of waste carelessly.